Pharmacogenetics of psoriasis: HLA‐Cw6 but not LCE3B/3C deletion nor TNFAIP3 polymorphism predisposes to clinical response to interleukin 12/23 blocker ustekinumab. (13th August 2013) - Talamonti, M.; Botti, E.; Galluzzo, M.; Teoli, M.; Spallone, G.; Bavetta, M.; Chimenti, S.; Costanzo, A.
Abstract : What's already known about this topic? Pharmacogenetic studies allowed us to link specific genetic features to clinical response or to side‐effects of conventional psoriasis therapies such as methotrexate, ciclosporin or acitretin. Little is known about the pharmacogenetics of biologics. What does this study add? We have studied the correlation between three psoriasis susceptibility genes and the response to ustekinumab, finding a significant association between HLA‐Cw6 and good clinical response to this drug. See also the Commentary by Wu and Reynolds Summary: Background: Our understanding of the genetic basis of predisposition to psoriasis is increasing exponentially due to the progress of genetic studies. However, so far little is known about genetic predisposition in relation to the response to psoriasis treatments. Recent data identified genetic predictors for the clinical outcome of conventional treatments such as methotrexate, acitretin and vitamin D derivatives, but few studies are available on genetic predictors of response to biologics. We hypothesized that genetic variations associated with increased risk of developing psoriasis may also act as predictors for the outcome of biologic therapy. Objectives: The aim of our study was to analyse the presence of three different psoriasis susceptibility genetic variations ( HLA‐Cw6 ; TNFAIP3 rs610604 polymorphism; LCE3B/3C gene deletions) in a cohort of patients affected by moderate to severe psoriasis under ustekinumab treatment. Our primary endpoint was to evaluate the association between Psoriasis Area and Severity Index (PASI) 75 response at week 12 and HLA‐Cw6 status. Methods: Fifty‐one patients were genotyped by standard methods and psoriasis severity (PASI score) was evaluated at day 0 and after 4, 12, 24 and 40 weeks of treatment. Results: We observed increased response to ustekinumab in Cw6‐positive (Cw6POS) patients [PASI 75 at week 12: 96·4% in Cw6POS vs. 65·2% in Cw6‐negative (Cw6NEG) patients; P  =   0·008]. In addition, we show that HLA‐Cw6POS patients responded faster to ustekinumab, 89·3% of them reaching PASI 50 at week 4, after a single injection (vs. 60·9% of HLA‐Cw6NEG patients). The superior response of HLA‐Cw6POS patients was maintained throughout the study period, reaching the highest statistical significance for PASI 75 at week 28 (96·35% Cw6POS vs. 72·7% Cw6NEG; odds ratio 9·8). Analysis of TNFAIP3 rs610604 polymorphism and LCE3B/3C gene deletions did not show any significant association with response to ustekinumab. Conclusions: Our observations underline the role of HLA‐Cw6 not only as a psoriasis susceptibility gene, but also as a pharmacogenetic marker of response to ustekinumab in psoriasis.